1998
DOI: 10.1074/jbc.273.5.3076
|View full text |Cite
|
Sign up to set email alerts
|

Human Small Intestinal Maltase-glucoamylase cDNA Cloning

Abstract: It has been hypothesized that human mucosal glucoamylase (EC 3.2.1.20 and 3.2.1.3) activity serves as an alternate pathway for starch digestion when luminal ␣-amylase activity is reduced because of immaturity or malnutrition and that maltase-glucoamylase plays a unique role in the digestion of malted dietary oligosaccharides used in food manufacturing. As a first step toward the testing of this hypothesis, we have cloned human small intestinal maltase-glucoamylase cDNA to permit study of the individual catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 50 publications
2
99
0
Order By: Relevance
“…Based on overlapping EST nucleotide sequences, alignment of deduced amino acid sequence with known ␣-glucosidases, and restriction mapping, we concluded that the 11 ESTs were derived from at least three different genes, which are illustrated in Figure 1. For each of the three genes, an EST was identified containing the peptide sequence WiDMNE, which is one of two signature peptides for ␣-glucosidases from Family 31 recognized by Nichols et al (1998). The Asp residue in this signature peptide is located in the active site as determined by labeling with conduritol B epoxide (Sugimoto et al, 1997).…”
Section: Arabidopsis Contains At Least Three ␣-Glucosidase Genesmentioning
confidence: 99%
“…Based on overlapping EST nucleotide sequences, alignment of deduced amino acid sequence with known ␣-glucosidases, and restriction mapping, we concluded that the 11 ESTs were derived from at least three different genes, which are illustrated in Figure 1. For each of the three genes, an EST was identified containing the peptide sequence WiDMNE, which is one of two signature peptides for ␣-glucosidases from Family 31 recognized by Nichols et al (1998). The Asp residue in this signature peptide is located in the active site as determined by labeling with conduritol B epoxide (Sugimoto et al, 1997).…”
Section: Arabidopsis Contains At Least Three ␣-Glucosidase Genesmentioning
confidence: 99%
“…Both enzymes can be divided into an N-terminal subunit (MGAM-N and SI-N) and a C-terminal subunit (MGAM-C and SI-C) (Nichols et al, 1998;Nichols et al, 2003). According to the carbohydrate-active enzymes (CAZY) classification system, all of these subunits belong to the glycoside hydrolase 31 family (GH31) subgroup 1, which contains the characteristic sequence WiDMNE in their catalytic centers (Ernst et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Correct protein folding of the individual monomers or subunits is required for optimal completion of these events. Many proteins are known not to go into dimers or heterodimers, such as the brush border proteins sucrase-isomaltase (SI) (7), angiotensin-converting enzyme (8), and maltase-glucoamylase (9). An interesting and common feature of these proteins is their composition of an even number of homologous domains.…”
mentioning
confidence: 99%